Identification and Evaluation of Logistics Operational Risk Using the Fmea Method at PT. XZY - Antonius Cahyono; Yunia Dwie Nurcahyanie (Aptisi Transactions On Technopreneurship (ATT), 2023)
The purpose of this study is to identify risks to operational factors in PT. XZY identifies and formulates existing handlers in PT. XZY related to risks to work operations. This study used the FMEA method. FMEA is a method used to perform analysis inductively, carried out repeatedly and systematically so that the process can be documented. Data was obtained using direct observation and interviews with logistics workers. Based on the results of problem identification and fmea calculation results, 19 operational risks were obtained in the logistics department of PT. XZY and varying RPN values, with the smallest value being 12 and the largest value being 729. Thus, it is concluded that the 3 highest risks in operations that can hinder work activities are limited product storage, improper placement of spare parts, and input errors in the system